FACTORS INFLUENCE ON THE EFFICIENCY OF LOGISTICS SYSTEMS OF THE REGION AND ENTERPRISES AND THEIR INTERCONNECTION (ON THE EXAMPLE OF THE LVIV REGION) (Development Service Industry Management, 2025)
Management of logistics systems at the level of regions and enterprises is one of the key problems for the development of the economy of Ukraine, in particular the Lviv region. In the context of globalization and integration into international transport corridors, the region faces the need to optimize internal logistics processes. However, there are serious challenges associated with the low level of automation, aging infrastructure and lack of qualified personnel. Increasing the efficiency of logistics systems requires not only improving the infrastructure, but also the introduction of modern technologies, such as automation, digitalization, real-time monitoring and other innovations, which allow significantly reducing costs and improving the accuracy and speed of operations.The study is aimed at analyzing factors affecting the management of logistics systems at the regional and enterprise levels, assessing the role of modern technologies in increasing the efficiency of logistics processes, and developing recommendations for optimizing logistics in the Lviv region.To achieve the goal of the study, methods of analyzing existing logistics practices at enterprises in the Lviv region were used, as well as methods of comparative and system analysis to assess the impact of various factors on the efficiency of logistics systems. The study of international experience in logistics management and the application of modern technologies helped to develop proposals for improving logistics processes in the region.The analysis showed that the main factors affecting the efficiency of logistics system management are: the quality of road and warehouse infrastructure, the level of automation, the use of modern digital technologies for monitoring and planning, as well as the training and qualification of personnel. Most enterprises in the region are currently only beginning to implement innovative technologies, such as automated warehouse management systems, RFID marking and IoT solutions for cargo tracking. At the same time, enterprises that actively use modern technologies demonstrate significant advantages in order processing speed, cost reduction and increased accuracy of operations.For enterprises in the Lviv region, the key areas of logistics process optimization are the implementation of modern ERP and TMS systems to automate management and transport operations, modernization of warehouse infrastructure using innovative technologies, such as automated warehouses, IoT sensors and Big Data for demand forecasting and route optimization.
Keywords: transport network quality; information technology development; cost optimization; inventory management; competitive advantages